Lossy Mode Resonance-based Aptasensor for CRP Detection. (2017) - Sanchez, P.; Zubiate, P.; Munoz, F.J.; Arregui, F.J.; Matias, I.R.; Zamarreño, C.R.
Abstract: In this work, a CRP detection by Aptasensor based on LMR is presented. A thin film of Tin Dioxide (SnO2 ) has been used as LMR generator, and the CRP Aptamer has blind onto the optical fiber to perform the measures.